Augmented reality board game using acceptance approach to enhance students' motivation - Irma Shayana Samaden; Universiti Teknikal Malaysia Melaka . Faculty of Information and Communication Technology (2025)
Board game incorporate distinct design characteristic that enhance player enjoyment. However, research on motivational elements in Augmented Reality Board Game (ARBG) remains limited. Therefore, a specific study needs to be conducted to explore how motivational elements in this type of game can be enhanced. This includes examining the characteristics and functions 0 f design as well a user acceptance, which are among the aspect that can enhance user motivation, particularly for those utilizing augmented reality platforms. In line with this, the purpose of this study is to develop a motivational model that integrates acceptance characteristics from the UT AUT acceptance model, motivation, and usability, which will subsequently be referred to as the U2SIC Model. The study employs a mixed-method approach, combining quantitative and qualitative methodologies across five phase: analysis, design and development, prototype testing, and evaluation. preliminary survey using questionnaires was conducted to determine key game design features. The de eloped ARBG application, Spiritual Journey Augmented Reality Board Game, was tested with 100 university students through pre- and post-tests to assess its effectiveness. The result indicate a significant increase in player motivation (mean value 4,09). Furthermore, user acceptance and usability testing yielded positive outcomes, confirming the model's effectiveness. In conclusion, the U2SlC model provides valuable insights for designing engaging AR-based board games. Future design should focus on increasing difficulty levels, improving aesthetic, and enhancing storytelling to maximize player motivation and user experience.
1. Introduction -- 2. Literature review -- 3. Methodology -- 4. Design and development -- 5. Finding and discussion -- 6. Conclusion
Thesis (Doctor of Philosophy) - Universiti Teknikal Malaysia Melaka, 2025
Includes bibliographical references (leaves 237-283)
Keywords: Universiti Teknikal Malaysia Melaka -- Dissertations; Universiti Teknikal Malaysia Melaka -- Faculty of Information and Communication Technology -- Dissertations; Augmented reality; Dissertations, Academic; Educational games; Motivation in education